The Digestive System of the Two-Spotted Spider Mite, Tetranychus urticae Koch, in the Context of the Mite-Plant Interaction - Bensoussan, Nicolas; Zhurov, Vladimir; Yamakawa, Sota; O'Neil, Caroline H.; Suzuki, Takeshi; Grbić, Miodrag; Grbić, Vojislava (Frontiers in Plant Science, 2018)
The two-spotted spider mite (TSSM), Tetranychus urticae Koch (Acari: Tetranychidae), is one of the most polyphagous herbivores, feeding on more than 1,100 plant species. Its wide host range suggests that TSSM has an extraordinary ability to modulate its digestive and xenobiotic physiology. The analysis of the TSSM genome revealed the expansion of gene families that encode proteins involved in digestion and detoxification, many of which were associated with mite responses to host shifts. The majority of plant defense compounds that directly impact mite fitness are ingested. They interface mite compounds aimed at counteracting their effect in the gut. Despite several detailed ultrastructural studies, our knowledge of the TSSM digestive tract that is needed to support the functional analysis of digestive and detoxification physiology is lacking. Here, using a variety of histological and microscopy techniques, and a diversity of tracer dyes, we describe the organization and properties of the TSSM alimentary system. We define the cellular nature of floating vesicles in the midgut lumen that are proposed to be the site of intracellular digestion of plant macromolecules. In addition, by following the TSSM’s ability to intake compounds of defined sizes, we determine a cut off size for the ingestible particles. Moreover, we demonstrate the existence of a distinct filtering function between midgut compartments which enable separation of molecules by size. Furthermore, we broadly define the spatial distribution of the expression domains of genes involved in digestion and detoxification. Finally, we discuss the relative simplicity of the spider mite digestive system in the context of mite’s digestive and xenobiotic physiology, and consequences it has on the effectiveness of plant defenses.